Religinė ir tautinė tapatybė Antano Baranausko poetinėje autorefleksijoje - Čiočytė, Dalia (Literatūra, 2015)
The article seeks to investigate Antanas Baranauskas’s self-conception from the theoretical perspective of phenomenology and theology of literature. The focus of attention are the poet’s early poems, as they demonstrate intensity of the poetical self-consciousness. Baranauskas interprets both religious and patriotic sense of the poetical writing. He contemplates the transcendental meaning of poetry, creates the link between romantic / Biblical prophet and himself as a poet, between the Christian concept of neighbour and national feelings. Baranauskas’s literary thought is ingenious and attentive to semantic undertones.